2021
DOI: 10.1108/bfj-03-2021-0214
|View full text |Cite
|
Sign up to set email alerts
|

Food choice drivers of potential lab-grown meat consumers in Australia

Abstract: PurposeTo examine the market potential for lab-grown meat (LGM) in Australia by: (1) determining consumers' willingness to consume LGM; (2) exploring heterogeneity in both consumers' willingness to consume LGM and food choice values; and (3) characterizing unique consumer clusters (segments) using socio-demographic, behavioral and psychosocial factors.Design/methodology/approachLatent class cluster analysis was conducted using online survey data obtained from a nationally representative sample of 1,078 Austral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…The main perceived benefits are animal welfare and environmental benefits, but more recently personal benefits such as health and food safety have also been cited. Previous studies have also confirmed that the acceptance of cultured meat is influenced by various socioeconomic characteristics such as gender, age, income, education level, and the household size of consumers [22,[24][25][26], but also by their culture/nationality [27][28][29]. Recent studies confirm the influence of consumers' diet (frequency of meat consumption) [30] and the influence of producers' organisational factors on consumers' acceptance of cultured meat [31].…”
Section: Introductionmentioning
confidence: 80%
“…The main perceived benefits are animal welfare and environmental benefits, but more recently personal benefits such as health and food safety have also been cited. Previous studies have also confirmed that the acceptance of cultured meat is influenced by various socioeconomic characteristics such as gender, age, income, education level, and the household size of consumers [22,[24][25][26], but also by their culture/nationality [27][28][29]. Recent studies confirm the influence of consumers' diet (frequency of meat consumption) [30] and the influence of producers' organisational factors on consumers' acceptance of cultured meat [31].…”
Section: Introductionmentioning
confidence: 80%
“…It is associated by the studies with higher willingness to try and consume novel food in n=47 studies: (Ali & Ali, 2022;Ardoin & Prinyawiwatkul, 2020;Asioli et al, 2022;Baker et al, 2016;Barsics et al, 2017;Barton et al, 2020;Baum et al, 2021;Bekker et al, 2017;Bieberstein et al, 2013;C. Bryant & Sanctorum, 2021;Caparros Megido et al, 2016;de Beukelaar et al, 2019;Franceković et al, 2021;Gallen et al, 2019;Garcez de Oliveira Padilha et al, 2021;Gurdian et al, 2021a;Hartmann et al, 2015;Herbert & Beacom, 2021;Higa et al, 2021;La Barbera et al, 2018;Lammers et al, 2019;Laureati et al, 2016;Lorini et al, 2021;Lupton & Turner, 2018b; M. C. Mancini & Antonioli, 2020; S. Mancini et al, 2019;Modlinska et al, 2021;Naranjo-Guevara et al, 2021;Onwezen et al, 2019;Palmieri et al, 2019;Poortvliet et al, 2019;Possidónio et al, 2021;Schäufele et al, 2019;Schlup & Brunner, 2018;Simion et al, 2020;Steenis & Fischer, 2016;Szejda et al, 2021;Tan et al, 2015;Tan, Tibboel, et al, 2017;Tan, van den Berg,...…”
Section: Familairity Values and Cultural Influencesmentioning
confidence: 99%
“…J. Bryant & Barnett, 2019;C. Bryant & Sanctorum, 2021;Circus & Robison, 2018;Egolf et al, 2019;Franceković et al, 2021;Garcez de Oliveira Padilha et al, 2021;Gorgitano et al, 2017;Klöckner et al, 2022;Laestadius & Caldwell, 2015;Lensvelt & Steenbekkers, 2014;Lupton & Turner, 2018a, 2018bOnwezen et al, 2019;Rosenfeld & Tomiyama, 2022;Ruby et al, 2015;Ruzgys & Pickering, 2020;Shaw & Mac Con Iomaire, 2019)Siegrist et al, 2018;Siegrist & Sütterlin, 2017;Slade, 2018;…”
unclassified
“…At present there is a lack of understanding of consumer segmentation related to the choice of cultured meat. As far as the authors know, only two studies have conducted a cluster analysis and recognised consumer segments based on perceptions towards different meat substitutes including cultured meat (de Oliveira Padilha et al, 2021;Possid onio et al, 2020). Therefore, a need exists to recognise and profile consumer segments specifically based on their choices with regard to cultured meat.…”
Section: Introductionmentioning
confidence: 99%